Sosialisasi Pencegahan Stunting di Desa Sampalan Tengah - Putu Riska Indah Mentari; Gusi Putu Lestara Permana; Ngakan Nyoman Kutha Krisnawijaya; I Gusti Ngurah Darma Paramartha; Adie Wahyudi Oktavia Gama (Lembaga Dongan Dosen, 2024)
Stunting is a condition in which toddlers exhibit insufficient height or length in relation to their age. Stunted toddlers are likely to face difficulties in achieving optimal physical and cognitive development in the future. The causes of stunting can be attributed to various factors, including socioeconomic conditions, maternal nutrition during pregnancy, infant illnesses, and inadequate nutritional intake during infancy. The community service activities conducted in Sampalan Tengah Village, Klungkung Regency, involve a stunting prevention socialization program carried out during toddler health posts (posyandu). The objectives of this community service initiative are to reduce the incidence of stunting in Sampalan Tengah Village, as well as to enhance community knowledge, awareness, and concern regarding stunting, while also promoting community creativity in stunting prevention through the processing of nutritious food based on local food resources.